Biocompatible Macroion/Growth Factor Assemblies for Medical Applications - Aneta Michna; Agata Pomorska; Ozlem Ozcan (Biomolecules, 2023)
Growth factors are a class of proteins that play a role in the proliferation (the increase in the number of cells resulting from cell division) and differentiation (when a cell undergoes changes in gene expression becoming a more specific type of cell) of cells. They can have both positive (accelerating the normal healing process) and negative effects (causing cancer) on disease progression and have potential applications in gene therapy and wound healing. However, their short half-life, low stability, and susceptibility to degradation by enzymes at body temperature make them easily degradable in vivo. To improve their effectiveness and stability, growth factors require carriers for delivery that protect them from heat, pH changes, and proteolysis. These carriers should also be able to deliver the growth factors to their intended destination. This review focuses on the current scientific literature concerning the physicochemical properties (such as biocompatibility, high affinity for binding growth factors, improved bioactivity and stability of the growth factors, protection from heat, pH changes or appropriate electric charge for growth factor attachment via electrostatic interactions) of macroions, growth factors, and macroion-growth factor assemblies, as well as their potential uses in medicine (e.g., diabetic wound healing, tissue regeneration, and cancer therapy). Specific attention is given to three types of growth factors: vascular endothelial growth factors, human fibroblast growth factors, and neurotrophins, as well as selected biocompatible synthetic macroions (obtained through standard polymerization techniques) and polysaccharides (natural macroions composed of repeating monomeric units of monosaccharides). Understanding the mechanisms by which growth factors bind to potential carriers could lead to more effective delivery methods for these proteins, which are of significant interest in the diagnosis and treatment of neurodegenerative and civilization diseases, as well as in the healing of chronic wounds.